Multicomponent synthesis of α-branched amines using organozinc reagents generated from alkyl bromides - Leroux, Baptiste; Beaufils, Alexis; Banchini, Federico; Jackowski, Olivier; Perez-Luna, Alejandro; Chemla, Fabrice; Presset, Marc; Le Gall, Erwan (Beilstein Journal of Organic Chemistry, 2024)
The use of alkylzinc bromides in the multicomponent Mannich reaction is described. Heteroleptic organozinc compounds were obtained in THF or 2-MeTHF by direct insertion of zinc dust into the C–Br bond of alkyl bromides. It was found that the presence of a stoichiometric amount of LiCl was essential for the efficiency of the subsequent three-component coupling with aldehydes and amines. A variety of primary, secondary, and tertiary organozinc reagents as well as secondary amines and aromatic aldehydes could be used for the straightforward preparation of α-branched amines. Interestingly, whereas previously reported work describing the preparation and reaction of organozinc iodides in acetonitrile showed higher reactivity of secondary organozinc reagents over primary ones, reactions in THF in the presence of LiCl led to opposite results, with higher reactivity of primary organozinc reagents.
Keywords: alkyl bromides; branched amines; Mannich reaction; multicomponent reaction; zinc